2015
DOI: 10.1080/19476337.2015.1042054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packaging method and cold-storage time on chicken meat quality

Abstract: (2016) Effect of packaging method and cold-storage time on chicken meat quality, CyTA -Journal of Food, 14:1, 41-46, DOI: 10.1080/19476337.2015 To link to this article: https://doi.org/10. 1080/19476337.2015 This study was performed to determine the effects of vacuum packaging (VP) and modified-atmosphere packaging (MAP) (CO 2 /N 2 = 3:7) on the physicochemical properties and sensory attributes in chicken breast meat during storage at 2ºC±0.5ºC for 5, 10 and 15 days. Results showed that storage time influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 16 publications
(16 reference statements)
5
37
0
4
Order By: Relevance
“…Drip loss was calculated and obtained by the adapted method of Marcinkowska‐Lesiak et al () according to the formula:DL=)(m1-m2m1×100%,where DL is an indicator of drip loss in percentage, m 1 the weight of raw material before storage and m 2 the weight of raw material after storage in g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drip loss was calculated and obtained by the adapted method of Marcinkowska‐Lesiak et al () according to the formula:DL=)(m1-m2m1×100%,where DL is an indicator of drip loss in percentage, m 1 the weight of raw material before storage and m 2 the weight of raw material after storage in g.…”
Section: Methodsmentioning
confidence: 99%
“…Drip loss was calculated and obtained by the adapted method of Marcinkowska-Lesiak et al (2016) according to the formula:…”
Section: Physicochemical Analysesmentioning
confidence: 99%
“…Therefore, to overcome the drawbacks, plant extracts could be added in combination with chemical preservatives, bacteriocins and with some other processing methods (Weerakkody, Caffin, Dykes, & Turner, ). Previous studies carried out in relation to extending the shelf life have evaluated the efficacy, safety, and stability using different packaging methods with marinated plant extracts (Alakomi et al, ; Kim et al, ; Marcinkowska‐Lesiak et al, ; Zhou, Xu, & Liu, ). Further, vacuum package with antimicrobial compounds can be adapted to exert a synergistic effect to extend the shelf of fresh chicken meat.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out in relation to extending the shelf life have evaluated the efficacy, safety, and stability using different packaging methods with marinated plant extracts (Alakomi et al, 2017;Kim et al, 2015;Marcinkowska-Lesiak et al, 2016;Zhou, Xu, & Liu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional value of poultry meat, its high protein content, and low fat content as well as its flavor make it attractive to consumers, who increasingly declare their preference for meat of chickens that have been produced in the system taking the greatest possible care of birds' welfare (Damaziak, Michalczuk, & Kurek, 2012;Marcinkowska-Lesiak et al, 2016;Michalczuk, Łukasiewicz, Zdanowska-Sąsiadek, & Niemiec, 2014;Popova, Ignatova, Petkov, & Stanišić, 2016;Puchała, Krawczyk, Sokołowicz, & Utnik-Banaś, 2015). Studies have shown that more than half of Britons polled assessed the animals' welfare as very important, and more than 70% of the surveyed citizens of the United States reported concern about the welfare of farm animals (Norwood & Lusk, 2011).…”
Section: Introductionmentioning
confidence: 99%